Efektivitas Pengelolaan Limbah Konstruksi Berbasis Konsep 3R (Reduce, Reuse, Recycle) pada Pekerjaan Superstruktur - Sera Marselina; Katarina Rini Ratnayanti (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The rapid growth of Indonesia's construction industry has increased construction waste generation, particularly in superstructure work such as columns, beams, floor slabs, formwork, reinforcement, and concrete casting. The 3R concept (Reduce, Reuse, Recycle) is recommended by various regulations, yet its field effectiveness requires further study. This study aims to determine the effectiveness of 3R-based construction waste management, identify waste types with management potential, and assess project actors' roles and perceptions. The study was conducted at the Pasar Baru Ciparay Development Project using a descriptive quantitative approach with a 5-point Likert-scale questionnaire administered to 70 respondents, tested for validity (Pearson product moment) and reliability (Cronbach's Alpha). Results show reduce effectiveness of 82%, reuse 87%, recycle 87%, and overall 3R effectiveness of 88%, averaging 86% (very effective category). The largest waste originated from formwork timber (30%) and reinforcement steel offcuts (29%).